(untitled) (Journal of Parents and Teachers, 2025)
The article is based on the importance of different types of memory, where we find "lifesaver" memory, comprehensive memory, and mechanical memory. It also highlights the key role of word association in memory retention, achieved through repetition, association, intensity, teleology, evaluation, extinction, and inhibition. Throughout the article, the use of mnemonics will be explored.